2021
DOI: 10.1186/s13690-021-00587-3
|View full text |Cite|
|
Sign up to set email alerts
|

Adverse childhood experiences and psychological distress among higher education students in Southeast Nigeria: an institutional-based cross-sectional study

Abstract: Background Exposure to adverse childhood experiences (ACEs) constitutes public health problems linked to adverse mental outcomes such as psychological distress during adulthood. This study examines the prevalence of ACEs and psychological distress and explores the association between ACEs and psychological distress and demographic factors among young adults. Methods We conducted a cross-sectional study of 330 students from May 2018 to July 2018. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…The Lasting Effects of Early Adversity and Updating Ability on the Tendency to Develop PTSD Symptoms Following Exposure to Trauma in Adulthood Adverse childhood experiences (ACEs) refer to a wide range of circumstances or events that pose a serious threat to a child's physical or psychological well-being and are one of the most consistent risk factors associated with adult mental disorders (Agbaje et al, 2021;Bellis et al, 2015;Bryant et al, 2020;Cleare et al, 2018;McLaughlin et al, 2013;Nelson et al, 2020;Sareen et al, 2013;Trotta et al, 2015). The current study aims to test the moderating role of cognitive flexibility on the tendency of individuals with different levels of exposure to ACEs to develop posttraumatic stress disorder (PTSD) following exposure to additional trauma in adulthood.…”
Section: Adversity Updating and Ptsdmentioning
confidence: 99%
“…The Lasting Effects of Early Adversity and Updating Ability on the Tendency to Develop PTSD Symptoms Following Exposure to Trauma in Adulthood Adverse childhood experiences (ACEs) refer to a wide range of circumstances or events that pose a serious threat to a child's physical or psychological well-being and are one of the most consistent risk factors associated with adult mental disorders (Agbaje et al, 2021;Bellis et al, 2015;Bryant et al, 2020;Cleare et al, 2018;McLaughlin et al, 2013;Nelson et al, 2020;Sareen et al, 2013;Trotta et al, 2015). The current study aims to test the moderating role of cognitive flexibility on the tendency of individuals with different levels of exposure to ACEs to develop posttraumatic stress disorder (PTSD) following exposure to additional trauma in adulthood.…”
Section: Adversity Updating and Ptsdmentioning
confidence: 99%
“…ACE exposure is significantly associated with psychological distress [18]. It is not surprising that the authors' study showed a significant relationship between ACEs and drinking alcohol in order to de-stress or discharge negative emotions.…”
Section: Discussionmentioning
confidence: 81%
“…In that study, parental education at a level lower than a Bachelor degree was associated with higher ACEs scores among children [14]. Similarly, in According to the authors, parental education may play a role of a protective factor against Adverse Childhood Experiences and provides a buffer from poor health outcomes among children and adolescents [17]. Conversely, Karatekin et al found no statistically significant links between parental education and ACEs among 321 American young adults [18].…”
Section: Factors Associated With Adverse Childhood Experiencesmentioning
confidence: 92%